Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
The equation appropriate for this is
[tex]a_{n}=a_{1}+(n-1)d[/tex]
Wherein [tex]_{n}[/tex] is the missing term, [tex]a_{1}[/tex] is the first number in the sequence, and [tex]d[/tex] is the difference between the numbers.
So[tex]a_{50}=4+(50-1)6[/tex]
[tex]a_{50}=4+(49*6)[/tex]
[tex]a_{50}=4+(294)[/tex]
[tex]a_{50}=298[/tex]
*Sorry for the error.
[tex]a_{n}=a_{1}+(n-1)d[/tex]
Wherein [tex]_{n}[/tex] is the missing term, [tex]a_{1}[/tex] is the first number in the sequence, and [tex]d[/tex] is the difference between the numbers.
So[tex]a_{50}=4+(50-1)6[/tex]
[tex]a_{50}=4+(49*6)[/tex]
[tex]a_{50}=4+(294)[/tex]
[tex]a_{50}=298[/tex]
*Sorry for the error.
298, also 4 is first term. 49 terms left. 49*6=294
294+4=298
294+4=298
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.